Analisis Yuridis Perlindungan Nelayan Tradisional Berbasis Blue Economy di Bengkulu - Randi Desta Putra; Farah Raihanah Fauziyyah; Yoni Gustiyana; Ema Septaria (AHKAM, 2026)
The limited number of studies on the synchronization of policies for protecting traditional fishers within the framework of the blue economy indicates the need for studies that examine the interrelationship among regulations, ecosystem degradation, economic inequality, and the sustainability of traditional fishers’ livelihoods. This study aimed to analyze the effectiveness of fisher protection regulations and explore sustainability-based economic empowerment strategies in the coastal areas of Bengkulu. This study used a descriptive qualitative approach, with the research location in the coastal areas of Bengkulu selected using purposive sampling. Data were collected through in-depth observation of conflicts over fishing area claims between trawl fishers and traditional fishers in Seluma Regency, Bengkulu Province, and were then analyzed using thematic analysis. The results showed that the dominant factors influencing the conflict were weak enforcement of sanctions against the use of trawl fishing gear and the absence of participatory supervision by the competent authorities, which prompted traditional fishers to take self-help actions to protect their fishing areas. This finding reinforces the theory of legal pluralism, which highlights the gap between formal state law and the practice of living law carried out by communities in the field. Thus, integrated supervision of coastal areas between the government and fishing communities is the key to reducing conflict and creating legal certainty for traditional fishers. The implications of this study include enriching the literature on maritime legal sociology in Bengkulu and providing practical recommendations for the Regional Government of Seluma Regency to strengthen fishing area zoning through regional regulations that accommodate the rights of traditional fishers.